The Effect of KatG S315t M. Tuberculosis Gene Mutation on Conversion Rate of MDR-TB Patients with Shorter-Course Treatment - Raden Ayu Linda Andriani; Zen Ahmad (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Background. Resistance to the INH drug is most often caused by a mutation of the KatG S315T M.Tb gene. MDR TB treatment with short-term WHO mixes using high-dose INH drugs is considered less effective in this mutation condition because it causes high resistance to INH. The effectiveness of MDR TB treatment can be seen from the sputum smear conversion rate. This study was aimed to determine the effect of the S315T katG gene mutation on the treatment response of patients with MDR TB who received WHO short-term alloys at Dr Moh Hoesin general hospital, Palembang, Indonesia. Method. This study uses observational analytic with a prospective cohort approach. The study subjects were MDR TB patients at Dr Moh Hoesin general hospital, Palembang, Indonesia, and a PCR-RFLP examination was performed to see the katG gene, followed by sputum smear evaluation at the end of the first and second months of treatment to assess the speed of conversion. Data analysis using SPSS 25 with the chi-square statistical test. Results. The frequency of katG S315T M.Tb gene mutations was 51.85%. The majority of MDR TB sufferers experience rapid conversion (92.59%). 64.29% of the katG S315T gene mutation group experienced sputum smear conversion after one month, 28.57% after two months, and 7.14% after three months of treatment. There was no significant difference in conversion speed in the two groups (p = 0.741). Conclusion. There was no effect of the S315T M.Tb katG gene mutation on the speed of sputum smear conversion of MDR TB patients who received short-term alloy treatment.